2013
DOI: 10.3390/ma6052059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Pretreatment of Rubberwood with White Rot Fungi for Enzymatic Hydrolysis

Abstract: The effects of biological pretreatment on the rubberwood (Hevea brasiliensis), was evaluated after cultivation of white rot fungi Ceriporiopsis subvermispora, Trametes versicolor, and a mixed culture of C. subvermispora and T. versicolor. The analysis of chemical compositions indicated that C. subvermispora had greater selectivity for lignin degradation with the highest lignin and hemicellulose loss at 45.06% and 42.08%, respectively, and lowest cellulose loss (9.50%) after 90 days among the tested samples. X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 36 publications
6
45
0
2
Order By: Relevance
“…selectively degrade lignin in EFBs. Nazarpour et al (2013) found by the FTIR analysis that there was chemical changes during incubation of rubberwood by Ceriporiopsis subvermispora i.e lignin degradation but only a little change on carbohydrate degradation. The high selectivity for lignin degradation suggests that the fungus secrete a higher activity of lignin-degrading enzymes than cellulose and hemicellulose, and is therefore white rot fungus treatment is www.ccsenet.org/mas Modern Applied Science Vol.…”
Section: Resultsmentioning
confidence: 92%
“…selectively degrade lignin in EFBs. Nazarpour et al (2013) found by the FTIR analysis that there was chemical changes during incubation of rubberwood by Ceriporiopsis subvermispora i.e lignin degradation but only a little change on carbohydrate degradation. The high selectivity for lignin degradation suggests that the fungus secrete a higher activity of lignin-degrading enzymes than cellulose and hemicellulose, and is therefore white rot fungus treatment is www.ccsenet.org/mas Modern Applied Science Vol.…”
Section: Resultsmentioning
confidence: 92%
“…Keempat jamur menunjukkan kecenderungan yang sama, yaitu mampu menyisihkan lignin. Hasil penelitian lain menunjukkan bahwa lignin pada kayu karet juga berhasil disisihkan oleh Trametes versicolor dengan selektivitas terhadap lignin antara 1,07 -1,16 (Nazarpour et al, 2013). Gambar 1.…”
Section: Biopulpingunclassified
“…for 30 and 45 days, could be due to an increase in cellulose crystallinity as a result of selective fungal degradation of amorphous components. 29 Overall, 15 days of fungal incubation was sufficient to improve the nal hydrolysis yield of untreated pine by 22.6%.…”
Section: Effects Of Fungal and Organosolv Pretreatments On Pine Digesmentioning
confidence: 99%